ADAPTATION OF SMES IN RUSSIAN KARELIA TO ECONOMIC RECESSION (CASE SORTAVALA) - Stupkina, Yulia (Karelia-ammattikorkeakoulu (Pohjois-Karjalan ammattikorkeakoulu), 2016)
The first aim of the research is to understand whether the global recession and Russian economic problems have influence on the business performance of small and medium enterprises in Sortavala (Russian Karelia). The second ones is to look at how companies have reacted to these changes and what kind of strategies they use to cope with the recession. The theoretical section includes marketing strategies that could be possible to use to cope with the recession. The empirical section includes the research concerning the economic development of both countries Russia and Finland. Moreover the impact on Finish-Russian business is presented. In the empirical section there is an analysis of the recession impact specifically on local business in Sortavala (Russian Karelia). The analysis is based on survey among companies that are located directly in the region. The research revealed that negative macroeconomic trends and imposed sanctions influenced the development of the trade relations between Russia and Finland and in most cases they have had a negative effect.